Prediction for cardiovascular disease by using artificial neural network system / Nik Anis Nik Ab Rahman - Nik Ab Rahman, Nik Anis (2012)
Prediction for Cardiovascular Disease by Using Artificial Neural Network System (PCVDANNS) is design to help paramedic and end user to learn and use this system easily. This research is to develop a PCVDANNS using cased based reasoning technique using main distance measure equation. The cased based reasoning is one of Artificial Intelligent technique that can be implement in many area. The input of this system wil be age,body mass index (BMI), blood pressure,body fat,boold sugar, smoking habit and family history.Then this system will diagnose by using the input to predict the value to make the ouput result.This reseach methodology consist of four phases which are theoretical study, architecture design, prototype development and documentation.Besides, to complete this reseach, more than 100 data patients get from Dungun Health Department to satisfy the advantage of this system.This system is a web-based system and developed using JAVA as programming language.In the future, it is recommended that the prototype can learn from experience.The accuracy of this prototype is about 60 percent.